Association Between Serious Psychological Distress and Loneliness During the COVID-19 Pandemic: A Cross-Sectional Study with Pregnant Japanese Women - Takeda T; Yoshimi K; Kai S; Inoue F (Dove Medical Press, 2021)
Takashi Takeda,* Kana Yoshimi,* Sayaka Kai, Fumi Inoue Division of Women’s Health, Research Institute of Traditional Asian Medicine, Kindai University, Osaka, 589-8511, Japan*These authors contributed equally to this workCorrespondence: Takashi TakedaDivision of Women’s Health, Research Institute of Traditional Asian Medicine, Kindai University, 377-2 Ohno-Higashi, Osaka-Sayama, Osaka, 589-8511, JapanTel +81-72-366-0221 (Ext. 3393)Fax +81-72-366-6661Email take@med.kindai.ac.jpPurpose: Pregnant women are vulnerable to stress. The coronavirus disease 2019 (COVID-19) has caused a global pandemic and created significant stress for many people. Social distancing to reduce the spread of COVID-19 has also reduced social interactions, which has increased social isolation and loneliness. Loneliness is thought to increase perceived stress, cause psychological distress, and increase the risk of mental illness, such as depression. This study examined the association between serious psychological distress (SPD) and loneliness during the COVID-19 pandemic in pregnant Japanese women.Patients and Methods: An internet survey of 1022 pregnant women in Japan was conducted between June 1 and July 21, 2021. The 6-item Kessler Psychological Distress Scale, 3-item Revised UCLA Loneliness Scale, and Fear of COVID-19 Scale were used as measurement tools. The prevalence of SPD was defined as a K6 score of ≥ 13.Results: The prevalence of SPD was 16.5%. Multivariate analysis revealed that the risk factors for SPD were younger age (odds ratio [OR] 1.05; 95% confidence interval [CI] 1.01 to 1.10; p = 0.020), history of abortion or miscarriages (OR 1.56; 95% CI 1.04 to 2.36; p = 0.034), unemployment (OR 1.67; 95% CI 1.14 to 2.45; p = 0.008), fear of COVID-19 (OR, 1.12; 95% CI, 1.08 to 1.17; p < 0.001), and loneliness (OR 1.53; 95% CI 1.38 to 1.70; p < 0.001).Conclusion: Pregnant women in Japan showed a high prevalence of SPD. Younger age, unemployment, history of abortion or miscarriages, fear of COVID-19, and loneliness were independently associated with SPD. Clinicians and health officials should pay particular attention to the psychological health of pregnant women during the COVID-19 pandemic.Keywords: stress, mental health, social isolation, maternal health